Barbell Deadlift Training Increases the Rate of Torque Development and Vertical Jump Performance in Novices. Issue 1 (January 2015) - Thompson, Brennan J.; Stock, Matt S.; Shields, JoCarol E.; Luera, Micheal J.; Munayer, Ibrahim K.; Mota, Jacob A.; Carrillo, Elias C.; Olinghouse, Kendra D.
Abstract : Abstract: Thompson, BJ, Stock, MS, Shields, JE, Luera, MJ, Munayer, IK, Mota, JA, Carrillo, EC, and Olinghouse, KD. Barbell deadlift training increases the rate of torque development and vertical jump performance in novices. J Strength Cond Res 29(1): 1–10, 2015—The primary purpose of this study was to examine the effects of 10 weeks of barbell deadlift training on rapid torque characteristics of the knee extensors and flexors. A secondary aim was to analyze the relationships between training-induced changes in rapid torque and vertical jump performance. Fifty-four subjects (age, mean ± SD = 23 ± 3 years) were randomly assigned to a control ( n = 20) or training group ( n = 34). Subjects in the training group performed supervised deadlift training twice per week for 10 weeks. All subjects performed isometric strength testing of the knee extensors and flexors and vertical jumps before and after the intervention. Torque-time curves were used to calculate rate of torque development (RTD) values at peak and at 50 and 200 milliseconds from torque onset. Barbell deadlift training induced significant pre- to post-increases of 18.8–49.0% for all rapid torque variables ( p < 0.01). Vertical jump height increased from 46.0 ± 11.3 to 49.4 ± 11.3 cm (7.4%; p < 0.01), and these changes were positively correlated with improvements in RTD for the knee flexors ( r = 0.30–0.37, p < 0.01–0.03). These findings showed that a 10-week barbell deadlift training program was effective at enhancing rapid torque capacities in both the knee extensors and flexors. Changes in rapid torque were associated with improvements in vertical jump height, suggesting a transfer of adaptations from deadlift training to an explosive, performance-based task. Professionals may use these findings when attempting to design effective, time-efficient resistance training programs to improve explosive strength capacities in novices.